Essential oils as anti-protozoal agents - Mojica, Elmer-Rico E. (Animo Repository, 2005)
The anti-protozoal effects of essential oils were examined using microplate-based in-vitro bioassays on axenically cultured trophozoites of Acanthamoeba sp. (a keratitis-causing amoeba) and Tetrahymena pyriformis (a test organism for cytotoxicity). Essential oils were extracted by steam distillation from leaves, fruits and other parts of 10 plant species: Citrus sinensis (orange), Citrofortunella mitis (syn. Citrus microcarpa, calamansi), Citrus poonensis (ponkan), Citrus reticulata (dalandan), Eucalyptus citriodora (eucalyptus), Zingiber officinale (ginger), Cananga odorata (ilang-ilang), Cymbopogon winterianus (citronella), Pandanus sp. (pandan) and Mentha piperita (peppermint). Of the 10 species, Citronella, dalandan and ponkan showed 100% anti-protozoal activity. Interestingly, extracts from plants of the citrus family showed homogeneity in toxicity profiles for both protozoans while ginger and pandan showed differential reactivities